2020
DOI: 10.1111/fare.12480
|View full text |Cite
|
Sign up to set email alerts
|

Left‐BehindChildren's Grandparent–Child and Parent–Child Relationships and Loneliness: A Multivariable Mediation Model

Abstract: ObjectiveThe current study tested the association between family relationships and left‐behind children's loneliness, as well as mediators of those associations.BackgroundThere is considerable concern in China about the psychological well‐being of rural children whose parents move to urban areas for work, so‐called left‐behind children. However, there have been inconsistent results in the research concerning loneliness for these children.MethodParticipants were Chinese left‐behind children from rural families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The results also showed that positive youth–parent relationships mitigated the adverse impact of coronavirus risk perception on youth internalizing problems. Consistent with the results of the present study, previous research indicated that more positive youth–parent relationships were associated with greater positive social, emotional, and behavioral outcomes (e.g., better peer relationships, prosocial behaviors), which in turn were negatively related to lower children and adolescents’ mental health challenges (Buist et al, 2017 ; Song et al, 2020 ; Wang et al, 2014 ). Quality of parenting relationships was associated with various externalizing problems such as antisocial behaviors and deviant peer associations (Wissink et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results also showed that positive youth–parent relationships mitigated the adverse impact of coronavirus risk perception on youth internalizing problems. Consistent with the results of the present study, previous research indicated that more positive youth–parent relationships were associated with greater positive social, emotional, and behavioral outcomes (e.g., better peer relationships, prosocial behaviors), which in turn were negatively related to lower children and adolescents’ mental health challenges (Buist et al, 2017 ; Song et al, 2020 ; Wang et al, 2014 ). Quality of parenting relationships was associated with various externalizing problems such as antisocial behaviors and deviant peer associations (Wissink et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…Grandparent-child cohesion, an important indicator reflecting the quality of the grandparent-child relationship, is considered to have a significant impact on left-behind children’s emotional adaptation (Li et al, 2021; Song et al, 2018, 2021; Zhao et al, 2016; Zhou et al, 2021). According to the intergenerational solidarity theory (Bengtson and Roberts, 1991), positive cohesion with grandparents may positively influence children’s daily emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Third, this study failed to identify the specific source of family support that caregivers or migrant parents offer. One study found that the quality of the parent–child relationship was more closely related to left‐behind children's loneliness than grandparent–child relationship quality (Song et al, 2021). Further work can explore the distinct roles that migrant parent(s) and stay‐behind caregivers can play in supporting left‐behind children.…”
Section: Discussionmentioning
confidence: 99%